Corporate expenditure on environmental protection - Stefanie A. Haller; Liam Murphy (The Economic and Social Research Institute (ESRI), 2010)
We examine the determinants of firm's current environmental expenditure and firm's capital investment in equipment for pollution control using a Heckman selection model. As regards current environmental expenditure, we find that larger, exporting firms and firms subject to the Integrated Pollution Prevention and Control directive are more likely to spend resources at all. Once the decision to commit resources has been taken, larger firms, firms that are foreign-owned, and firms that report low shares of water and refuse charges in turnover have higher absolute levels of environmental expenditure. With respect to investment in equipment for pollution control, we find that energy intensive and exporting firms are more likely to invest at all. Once the decision to invest has been taken, larger firms and firms that report high water and refuse charges invest more in equipment for pollution control. This suggests that the firms for whom environmental concerns are most costly in terms of production and image do most to address them.
Keywords: 330; environmental expenditure; capital expenditure on pollution abatement; firm-level analysis; manufacturing.; Umweltschutzinvestition; Strategisches Management; Betriebliche Investitionspolitik; Betriebsgröße; Multinationales Unternehmen; Eigentümer; Theorie